Exploring the Integration of Digital Media in Islamic Early Childhood Education: Evidence from Kindergartens in Pontianak City - Ramadani, Laili; Kardi, Juliwis; Khairani Ismail , Nurul; Salina Samaun, Siti; Hamzah, Nur (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This study aims to analyze the integration of digital media in Islamic education in early childhood in kindergarten in Pontianak City, West Kalimantan Province by highlighting that teachers currently still have challenges in using technology.Design/methods/approach – This study uses qualitative research with a case study approach through observation, interviews, and documentation. This research was conducted in the city of Pontianak, West Kalimantan Province from September 11 to September 20, 2024. Data analysis includes data collection, condensation, presentation, and conclusion.Findings – The findings of this study in integrating digital media in Islamic education are still difficult for teachers so that in classroom learning activities they still use conventional methods in educating early childhood in kindergarten. In the learning process, the educational environment does not support the use of technology in learning and play activities in kindergarten. However, there is an opportunity to realize the integration of digital media in Islamic education in kindergarten because teachers consider this integration very important in learning in kindergarten.Research implications/limitations – Technology in Islamic education has a significant impact on the learning process for early childhood in kindergarten. This study is still limited to qualitative research, so other methods are needed to add to the findings related to technology in early childhood.Practical implications – This study shows that the integration of digital media in early childhood education in kindergarten still has challenges in using technology. teachers still experience difficulties, so that in classroom learning activities they still use conventional methods in educating early childhood in kindergarten. In addition, in the learning process, the educational environment does not support the use of technology in learning and playing activities in kindergarten.Originality/value – This research serves as an initial foundation for the development of a digital-based curriculum that is relevant to Islamic values and the characteristics of early childhood development. This research provides a new perspective on the utilization of digital media in Islamic education to improve the quality of learning and the relevance of teaching methods in kindergarten.Paper type Case study